IMPROVING STUDENTS' VOCABULARY MASTERY BY USING WORD SQUARE TECHNIQUE TO STUDENTS OF SMP METHODIST 1 PALEMBANG - Jenny Elvinna Manurung; Heru Setiawan; Febby Gresia Sianturi (Universitas Tridinanti Palembang, 2021)
The objective of this study to find out whether or not there was any significant difference on vocabulary mastery between students who were taught by using Word Square technique and those who were not. This study used quasi experimental. The population of this study was the eighth grade students of SMP Methodist 1 Palembang. The researchers used purposive sampling. There were 43 students as the sample. Each class consisted of students from VIII.A and 22 students from VIII.B. The researcher used paired sample t-test to compare the pretest and posttest result in experimental and control group. The result revealed that the significance (2-tailed) was 0.000, which is lower than alpha value 0.05, then t- obtained value = 5.340 was higher than t-table 2.086. In conclusion, the use of Word Square technique was effective to improve students' vocabulary mastery at the eighth grade students of SMP Methodist 1 Palembang. The data was analyzed by using independent sample t-test. The result showed that t-obtained 3.121 was higher than t-table 2.020 with degree of freedom (df=41) and the significant 2-tailed was 0.003. Therefore, there was a significant difference on vocabulary mastery between the students who were taught by using Word Square technique and those who were not.Keywords: Word Square Technique, Vocabulary Mastery